The anaerobic linalool metabolism in Thauera linaloolentis 47 Lol. Issue 1 (December 2016) - Marmulla, Robert; Cala, Edinson; Markert, Stephanie; Schweder, Thomas; Harder, Jens
Abstract Background The betaproteobacteriumThauera linaloolentis 47LolT was isolated on the tertiary monoterpene alcohol (R, S )-linalool as sole carbon and energy source under denitrifying conditions. Growth experiments indicated the formation of geraniol and geranial. Thus, a 3, 1-hydroxyl-Δ1 -Δ2 -mutase (linalool isomerase) activity may initiate the degradation, followed by enzymes of the acyclic terpene utilization (Atu) and leucine/isovalerate utilization (Liu) pathways that were extensively studied inPseudomonas spp. growing on citronellol or geraniol. Results A transposon mutagenesis yielded 39 transconjugants that could not grow anaerobically on linalool and nitrate in liquid medium. The deficiencies were apparently based on gene functions required to overcome the toxicity of linalool, but not due to inactivation of genes in the degradation pathway. Growing cultures formed geraniol and geranial transiently, but also geranic acid. Analysis of expressed proteins detected several enzymes of the Atu and Liu pathways. The draft genome ofT. linaloolentis 47LolT hadatu andliu genes with homology to those ofPseudomonas spp.. Conclusion The in comparison to monoterpenes larger toxicity of monoterpene alcohols is defeated by several modifications of the cellular structure and metabolism inThauera linaloolentis 47LolT . The acyclic terpene utilization pathway is used inT. linaloolentis 47LolT during growth on (R, S )-linalool and nitrate under anoxic conditions. This is the first experimental verification of an active Atu pathway outside of the genusPseudomonas .